Biometry of Genitalia, Incidence of Gynecological Disorders and Pregnancy Loss in Black Bengal Goat : An Abattoir Study - Anup Kumar Talukder; Md. Ataur Rahman; Md. Taimur Islam; Abu Nasar Md. Aminoor Rahman (The Korean Society of Animal Reproduction and Biotechnology, 2015)
This study was aimed to determine the biometry of genital organs, incidence of gynecological disorders and pregnancy loss in Black Bengal goat (Capra hircus). Genitalia of 118 does were collected from local abattoirs. Biometric parameters of genital organs were measured and gross and histopathological examinations were carried out for detection of abnormalities. For gravid uterus, age of the fetus was determined by measuring crown-rump length. There was no significant difference in the length, width and weight of right and left ovaries (P>0.05). However, the number of follicles between left (5.3 ± 2.3) and right ovaries (7.4 ± 2.7) varied significantly (P<0.05). The mean length of right fallopian tube and uterine horn were not varied with those of left fallopian tube and uterine horn. The length of uterine body, cervix and vagina were 1.3 ± 0.1 cm, 3.3 ± 0.5 cm and 6.8 ± 1.3 cm, respectively. Overall, 29 (24.6%) genitalia had abnormalities. Fifteen genitalia (12.7%) had ovarian abnormalities including ovaro-bursal adhesions (6.8%), parovarian cyst (5.1%) and follicular cyst (0.9%). Uterine abnormalities were found in 12 genitalia (10.2%) and predominant uterine lesion was endometritis (6.8%) followed by adenomyosis (1.7%), hemorrhagic lesion on endometrial surface (0.9%) and cyst in broad ligament (0.9%). In addition, cyst in fallopian tube (0.9%) and vagina (0.9%) were recorded. The proportion of slaughtered pregnant goats was 15.3% (18/118). The pregnancy wastage was highest in the first month (50.0%) followed by second (33.3%) and third (16.7%) month. It can be concluded that ovaro-bursal adhesions, parovarian cyst and endometritis are the gynecological disorders of major concern in Black Bengal goat.